Paradoxical antidepressant effects of alcohol are related to acid sphingomyelinase and its control of sphingolipid homeostasis - Müller, Christiane; Kalinichenko, Liubov; Tiesel, Jens; Witt, Matthias; Stöckl, Thomas; Sprenger, Eva; Fuchser, Jens; Beckmann, Janine; Praetner, Marc; Huber, Sabine; Amato, Davide; Mühle, Christiane; et al. (Acta Neuropathologica, 2016)
Alcohol is a widely consumed drug that can lead to addiction and severe brain damage. However, alcohol is also used as self-medication for psychiatric problems, such as depression, frequently resulting in depression-alcoholism comorbidity. Here, we identify the first molecular mechanism for alcohol use with the goal to self-medicate and ameliorate the behavioral symptoms of a genetically induced innate depression. An induced over-expression of acid sphingomyelinase (ASM), as was observed in depressed patients, enhanced the consumption of alcohol in a mouse model of depression. ASM hyperactivity facilitates the establishment of the conditioned behavioral effects of alcohol, and thus drug memories. Opposite effects on drinking and alcohol reward learning were observed in animals with reduced ASM function. Importantly, free-choice alcohol drinking-but not forced alcohol exposure-reduces depression-like behavior selectively in depressed animals through the normalization of brain ASM activity. No such effects were observed in normal mice. ASM hyperactivity caused sphingolipid and subsequent monoamine transmitter hypo-activity in the brain. Free-choice alcohol drinking restores nucleus accumbens sphingolipid- and monoamine homeostasis selectively in depressed mice. A gene expression analysis suggested strong control of ASM on the expression of genes related to the regulation of pH, ion transmembrane transport, behavioral fear response, neuroprotection and neuropeptide signaling pathways. These findings suggest that the paradoxical antidepressant effects of alcohol in depressed organisms are mediated by ASM and its control of sphingolipid homeostasis. Both emerge as a new treatment target specifically for depression-induced alcoholism.
EVALuna2:3919